On the socio-technical potential for onshore wind in Europe: A response to critics. (April 2021) - Enevoldsen, Peter; Permien, Finn-Hendrik; Bakhtaoui, Ines; von Krauland, Anna-Katharina; Jacobson, Mark Z.; Xydis, George; Sovacool, Benjamin K.; Valentine, Scott V.; Luecht, Daniel; Oxley, Gregory
Abstract: This paper discusses and rebuts McKenna et al.'s (2020, hereinafter M20) critique of the European wind power potential analysis of Enevoldsen et al. (2019, hereinafter E19). This paper rebuts M20's five claims regarding 1) potential definitions and conceptualizations of sociotechnical systems, 2) incomplete literature review, 3) opaque and incorrect use of input data, 4) oversimplified methods without validation, and 5) lack of consideration for some recent results. The five claims have been discussed using additional literature reviews, data from real operational European onshore wind turbines, elaborations of the research methodologies, as well as the justifications for the selected data and materials in E19, and finally thorough examinations of the proposed justifications for the five claims by M20 from where the majority was grounded in previous publications by the author group behind M20. We conclude that the relevant claims of M20 are incorrect or unproven, so the results of E19 stand. Highlights: A response to the five critique points from McKenna et al. (2020) is brought forward. The paper highlights the errors associated with McKenna et al. (2020)'s state-of-the-art. The study highlights why Enevoldsen et al. (2019) have applied the term sociotechnical in a proper manner. The study examines previous studies and explains why their results might differ from Enevoldsen et al. (2019).